Between Script and Scripture: Performance Criticism and Mark's Characterization of the Disciples - Eberhart, Zechariah (Biblical Interpretation Series, 2024)
Utilizing Performance Criticism, this volume explores how the traditional literary configurations of the disciples' characterization in the Gospel of Mark are complicated by considerations of the oral milieu of the first-century.